A 'coloured' history, a black future: contesting the dominant representations in the media through hip-hop beats - Marco, Derilene (My University, 2009)
This research will critically analyse “conscious” hip-hop music and the way in which it contests media and mainstream ideas in the media. Conscious hip-hop refers to rap music that critically engages with hegemonic discourses and popular culture. It is framed and named in this manner by both the performers/ artists themselves as well as by leading hip-hop scholars within South Africa and globally. This research uses the music of Godessa and Brasse Vannie Kaap to interrogate representations of Black identities and gender in society.
M.A.(Media Studies), Faculty of Humanities, University of the Witwatersrand, 2009
Keywords: media representations; hip-hop; gender; race